An international dynamic term structure model with economic restrictions and unspanned risks - Gregory H. Bauer; Antonio Diez de los Rios (Bank of Canada, 2012)
We construct a multi-country affine term structure model that contains unspanned macroeconomic and foreign exchange risks. The canonical version of the model is derived and is shown to be easy to estimate. We show that it is important to impose restrictions (including global asset pricing, carry trade fundamentals and maximal Sharpe ratios) on the prices of risk to obtain plausible decompositions of forward curves. The forecasts of interest rates and exchange rates from the restricted model match those from international survey data. Unspanned macroeconomic variables are important drivers of international term and foreign exchange risk premia as well as expected exchange rate changes.
Keywords: E43; F31; G12; G15; 330; Asset Pricing; Exchange rates; Interest rates